The Photostability of Novel Boron Hydride Blue Emitters in Solution and Polystyrene Matrix - Ševčík, Jakub; Urbánek, Pavel; Hanulíková, Barbora; Čapková, Tereza; Urbánek, Michal; Antoš, Jan; Londesborough, Michael G S; Bould, Jonathan; Ghasemi, Bita; Petřkovský, Lukáš; Kuřitka, Ivo (Materials (Basel, Switzerland), 2021)
In recent work, the boron hydride anti-B18H22 was announced in the literature as a new laser dye, and, along with several of its derivatives, its solutions are capable of delivering blue luminescence with quantum yields of unity. However, as a dopant in solid polymer films, its luminescent efficiencies reduce dramatically. Clarification of underlying detrimental effects is crucial for any application and, thus, this contribution makes the initial steps in the use of these inorganic compounds in electrooptical devices based on organic polymer thin films. The photoluminescence behavior of the highly luminescent boron hydrides, anti-B18H22 and 3,3',4,4'-Et4-anti-B18H18, were therefore investigated. The quantum yields of luminescence and photostabilities of both compounds were studied in different solvents and as polymer-solvent blends. The photophysical properties of both boranes are evaluated and discussed in terms of their solvent-solute interactions using photoluminescence (PL) and NMR spectroscopies. The UV degradability of prepared thin films was studied by fluorimetric measurement. The effect of the surrounding atmosphere, dopant concentration and the molecular structure were assessed.
Keywords: anti-B18H22; OLED; boronhydride emitters; photostability